Solusi Gangguan Smartphone Addiction Berdasarkan Pendekatan Psikologi Islam - Hs, Aprianda Helni; Hidayat, Bahril (UIR Press, 2021)
ABSTRACT Adolescent at this point very close to the rapid technological growth. Adolescent are a primary target for debatable features inside the smartphone, which makes it easier for the youth to become addicted to the smartphone usage, and this of course, also encourages learning in the youth to become weak that results in a drop in academic achievement. Previous studies have explained that adolescents depend heavily on their smartphones, as well as on the features available inside the smartphone. It also certainly had an impact on academic achievement, their ability to achieve good academic achievement was weak, they were not motivated to get a good achievement on their academic. In this case, youth should pay more attention to the time of their smartphone use, youth should also have internal motivation, parents, teachers, and friend so that youth have the proper fighting power to improve academic achievement. On the other side, a homepical method is used as a solution to the smartphone. The application of reading a digital Quran application in away of data collection, data reduction, data presentation, and a withdrawal of conclutions or otherwise know by miles and huberman interactive models has yielded results from where reading the Quran could direct youth to use smartphones on positive things. Students or adolescents affected by smartphone addictions in the interview express better changes in themselves and want to continue reading Quran applications on their order to break from their smartphone addictions. Keywords: Smartphone Addiction, Fighting power, Academic Achievement, Adolescence ABSTRAK Remaja pada zaman sekarang merupakan orang yang sangat dekat dengan perkembangan teknologi yang sangat pesat. Remaja merupakan sasaran utama pengembangan fitur-fitur yang ada di dalam Smartphone, dengan ini memudahkan remaja menjadi candu pada penggunaan Smartphone dan tentunya hal ini juga menimbulkan daya juang belajar pada remaja menjadi lemah yang mengakibatkan penurunan pada prestasi akademik. Artikel ini menggunakan metode studi kepustakaan sebagai pendekatan kualitatif deskriptif yang menggambarkan fenomena adiksi smartphone (ponsel pintar) pada siswa atau remaja. Dalam hal ini, remaja harus lebih memperhatikan waktu penggunaan Smartphone mereka. Remaja juga harus mendapatkan metode belajar yang tepat untuk mengatasi adiksi ponsel pintar. Selain itu, metode keislaman dipergunakan sebagai solusi mengatasi smartphone addiction. Penerapan membaca aplikasi al-Quran digital yang dilakukan dengan cara pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan atau yang dikenal dengan teknik analisis data pada konsep miles and huberman interactive model berhasil menunjukkan hasil tentang penerapan membaca al-Quran mampu mengarahkan remaja untuk menggunakan smartphone kepada hal yang positif. Siswa atau remaja yang terkena adiksi smartpone menyatakan perubahan lebih baik pada diri mereka dan ingin terus membaca aplikasi al-Quran pada ponsel mereka untuk dapat berhenti dari kecanduan smartphone mereka. Kata Kunci: Smartphone Addiction, Daya Juang, Prestasi Akademik, Remaja